Case report: Gene mutation analysis and skin imaging of isolated café-au-lait macules - Zhong, Zhenyu; Yang, Tianhui; Liu, Siqi; Wang, Shan; Zhou, Shan; Du, Shuli; Zheng, Liyun; Wang, Xiuli; Wang, Hui; Wang, Yifan; Gao, Min (Frontiers in Genetics, 2023)
Background: Café-au-lait macules (CALMs) are common birthmarks associated with several genetic syndromes, such as neurofibromatosis type 1 (NF1). Isolated CALMs are defined as multiple café-au-lait macules in patients without any other sign of NF1. Typical CALMs can have predictive significance for NF1, and non-invasive techniques can provide more accurate results for judging whether café-au-lait spots are typical. Objectives: The study aimed to investigate gene mutations in six Chinese Han pedigrees of isolated CALMs and summarize the characteristics of CALMs under dermoscopy and reflectance confocal microscopy (RCM). Methods: In this study, we used Sanger sequencing to test for genetic mutations in six families and whole exome sequencing (WES) in two families. We used dermoscopy and RCM to describe the imaging characteristics of CALMs. Results: In this study, we tested six families for genetic mutations, and two mutations were identified as novel mutations. The first family identified [NC_000017.11(NM_001042492.2):c.7355G>A]. The second family identified [NC_000017.11(NM_001042492.2):c.2739_2740del]. According to genotype-phenotype correlation analyses, proband with frameshift mutation tended to have a larger number of CALMs and a higher rate of having atypical CALMs. Dermoscopy showed uniform and consistent tan-pigmented network patches with poorly defined margins with a lighter color around the hair follicles. Under RCM, the appearance of NF1 comprised the increased pigment granules in the basal layer and significantly increased refraction. Conclusion: A new heterozygous mutation and a new frameshift mutation of NF1 were reported. This article can assist in summarizing the properties of dermoscopy and RCM with CALMs.